Does Profitability Mediate the Relationship between Financial Characteristics and Firm Value? Evidence from Islamic Capital Markets - Sokhikhatul Mawadah; Muhammad Firman Khoiruddin; Dessy Noor Farida (Journal of Islamic Economics Management and Business (JIEMB), 2026)
This study aims to analyze the effect of liquidity, leverage, and company size on company value with profitability as an intervening variable. This study focuses on companies listed on the Jakarta Islamic Index (JII) for the 2021-2023 period. The research method uses a quantitative approach with a purposive sampling technique, resulting in 18 companies as samples. Data analysis was carried out using multiple linear regression and the Sobel test to test the mediation effect. The results of the study indicate that liquidity has no significant effect on company value, leverage has a significant negative effect on company value, and company size has a significant positive effect on company value. Profitability is proven to mediate the relationship between leverage and company value, but does not mediate the relationship between liquidity and company size and company value.